Elimination of Odours from the Gaseous Phase on Cr- and Fe-modified Y-type Zeolites - Zenon Sarbak (Adsorption Science & Technology)
Modified NaY-type zeolites, in which a portion of the sodium ions had been exchanged for chromium(III) or iron(III) ions, were studied as adsorbents. The modified zeolites were tested with respect to the adsorption of n-butylamine or n-butylthiol via the pulse method employing a column micro-adsorber directly attached to a gas chromatograph. Thus, 200 mg portions of the adsorbent were activated by heating at 400°C for 2 h after which the temperature was decreased to 200°C. The column was held at this temperature for 1 h and then 10 μl portions of n-butylamine and n-butylthiol were injected on to it at 15-min intervals. It was found that the zeolites containing iron(III) ions were much more effective as adsorbents (by 30%) than those containing chromium ions, with this difference reaching 60% in the case of n-butylthiol. Furthermore, zeolites containing iron(III) ions underwent much less deactivation than those with chromium(III) ions. Increasing the iron → sodium or chromium → sodium ion exchange led to increased adsorption of the organic compounds studied. It was shown that Y-type zeolites modified with iron(III) are effective adsorbents for deodorising atmospheric air.